Implementasi Algoritma Simple Additive Weighting Untuk Sistem Seleksi Beasiswa Terintegrasi - Muchlis, Lita Sari; Fitra Kasma Putra; Abdurrahman Niarman; Zihnil Afif; Dilha Japami; Eva Rahmayanti Br Saragih; Nindya Dwi Putri (The Indonesian Journal of Computer Science, 2024)
Simple Additive Weighting (SAW) in Decision Support Systems effectively identifies the optimal alternative by assessing criteria weights and ratings. This study aims to apply the SAW method for selecting scholarship recipients at BAZNAS Tanah Datar Regency, replacing the inefficient manual process. Selection criteria include parental income, number of dependents, academic performance, home ownership, and asset ownership. System development follows a prototyping approach, starting with user requirement identification, creating initial prototypes, and incorporating user feedback. We conducted final testing using Black Box Testing and the System Usability Scale (SUS), which resulted in a 100% Black Box score for expected functionality and a SUS score of 86, indicating high usability and user acceptance. Results show that the SAW method improves objectivity, reduces manual errors, and speeds up selection, resulting in a fairer, more efficient process. The system will undergo regular maintenance and evaluation to ensure optimal performance.